How is The Implementation of Diagnostic Tests in Biology Learning in South Sumatra? - Safira Permata Dewi; Yenni Lidyawati; Elvira Destiansari (Postgraduate, University of Mataram, 2022)
Diagnostic tests have a very important role to provide information about the strengths and weaknesses of students related to a concept to be studied. This study aims to obtain an overview of the implementation of diagnostic tests carried out by Biology teachers in South Sumatra Province using the survey method. This study involved 86 Biology teachers in South Sumatra Province. Samples were taken using the convenience sampling method. Data collection by using e-questionnaire distributed through Google Form. The e-questionnaire consists of 25 questions developed from standard indicators of assessment, including planning, method selection, test instrument development, test implementation, test result management, test results reporting and the implications of these test results in the biology learning process in schools. The results of this study indicate that Biology teachers in South Sumatra have carried out routine diagnostic tests. The development of this diagnostic test instrument has also referred to the learning objectives and the results of the diagnostic test have been used to determine the methods, strategies, and approaches used in the learning process. Although in general the implementation of diagnostic tests in Biology learning is good, but the implementation and management of diagnostic tests that are very close to the learning process is feared will not have a significant effect on the implementation of the learning process in schools.